Benefits of a WeChat-based multimodal nursing program on early rehabilitation in postoperative women with breast cancer: A clinical randomized controlled trial. (June 2020) - Zhou, Kaina; Wang, Wen; Zhao, Wenqian; Li, Lulu; Zhang, Mengyue; Guo, Pingli; Zhou, Can; Li, Minjie; An, Jinghua; Li, Jin; Li, Xiaomei
Abstract: Background: Primary treatments for early-stage breast cancer can cause adverse effects, such as pain, fatigue, and sleep disturbance, that can markedly affect the patients' health-related quality of life. Objective: This study aimed to evaluate the benefits of a WeChat-based multimodal nursing program on early rehabilitation in postoperative women with breast cancer. Design: Clinical randomized controlled trial. Setting: Surgical breast cancer department of a general hospital in Shaanxi Province, China. Participants: Women with breast cancer were recruited via convenience sampling. The inclusion criteria were (1) age ≥18 years, (2) newly diagnosed with breast cancer, (3) stage I–III disease, and (4) indicated for surgery with adjuvant therapy. Exclusion criteria were (1) comorbidity with other malignant tumors and infections and (2) cognitive or psychiatric disorders. Methods: We recruited patients with breast cancer and randomly allocated them to the intervention ( n = 56) and control ( n = 55) groups. The former was subjected to the WeChat-based multimodal nursing program plus routine nursing care for 6 months, whereas the latter received only routine nursing care. The primary endpoint (health-related quality of life) and secondary endpoints (pain, fatigue, and sleep) were measured using the Functional Assessment of Cancer Therapy-Breast version 4.0 (FACT-Bv4.0) and the Numerical Rating Scale at 4 time points (i.e., pre-surgery and 1, 3, and 6 months post-surgery). Results: The intervention group had significantly improved total FACT-Bv4.0 scores owing to the effects of group ( F = 16.28, P < 0.001), time ( F = 28.82, P < 0.001), and group-time interaction ( F = 5.35, P = 0.001). Similar improvements were also found in social/family well-being and functional well-being ( P < 0.05). Emotional well-being was improved based on the effects of time ( F = 42.12, P < 0.001) and group-time interaction ( F = 10.20, P < 0.001). The 'breast cancer-specific subscale for additional concerns' was affected by group ( F = 21.55, P < 0.001) and time ( F = 28.96, P < 0.001), whereas physical well-being was only affected by time ( F = 35.39, P < 0.001). Pain, fatigue, and sleep were not significantly influenced by group effects. Conclusions: We found a significant improvement in the health-related quality of life of postoperative women with breast cancer who used the WeChat-based multimodal nursing program during early rehabilitation. This demonstrated that the program is an effective intervention for postoperative rehabilitation in such patients. Findings of the study will provide evidence for eHealth services in clinical and transitional nursing care.